IMPLEMENTATION OF EDUCATIONAL SNAKE AND LADDER GAMES IN IMPROVING THE UNDERSTANDING OF INTEGER OPERATIONS IN ANMOK LEARNING GROUPS - Dhiki, Yasinta Yenita; Bupu, Lusia Valentina; Idung, Meli Fatima; Bara, Marista Erigenia Seruni (LPPM Universitas Flores, 2025)
This community service project aims to describe the application of educational snakes and ladders games in enhancing children's understanding of integer operations within the Anmok Learning Group in Rewarangga Village. Using a qualitative descriptive approach with 20 elementary school students who are members of the Anmok Learning Group, data were collected through observation, interviews, tests, and documentation. The results show that the educational snakes and ladders game effectively improves understanding of integer concepts, learning motivation, and social values such as cooperation and sportsmanship. Therefore, this game serves as a fun and engaging learning medium that also supports the development of children's numeracy literacy in non-formal learning environments. The use of educational snakes and ladders games can be positioned as one of the innovative learning strategies relevant to non-formal education contexts. This medium serves as an engaging learning tool that aligns instructional goals while supporting efforts to enhance children's numeracy literacy within the community. These findings recommend that educators and non-formal learning facilitators incorporate educational games in a planned and systematic manner as an alternative learning approach adapted to the characteristics of learners.